Visualizing the Effect of COVID-19 Pandemic in India using Python - P. Bramhanjali, V. Keerthana Devi, R. Sunayana, Dr. K. Sita Kumari (International Journal of Advanced Science and Technology, 2020)
The sudden outbreak of the promptly spreading novel coronavirus (COVID-19) has an intense impact on the health of all the individuals around the globe. The governments of all the respective nations have declared this pandemic as a worldwide health emergency and they are taking effective prevention and control measures by strictly recommending the civilians to stay indoors and assuring that the individuals are following necessary precautions. In the past few months, the novel coronavirus has been very uncontrollable and led to the transmission of infection at a very faster rate. There are a lot of confirmed cases reported but there are no accurate estimates. Multiple datasets have been used in this paper to determine the state-wide cases registered in India, cases that are registered based on the age groups, and the number of confirmed, recovered as well as the deaths that are reported up to date. This paper mainly focuses on analysing the data collected from multiple sources and visualize it efficiently. It also presents the insights of how COVID-19 has immensely affected the people in India.